Efektivitas Pemungutan Pajak Hotel Dalam Meningkatkan Penerimaan Pajak Daerah di Kota Bekasi Tahun Anggaran 2018-2023 - Wahyudin, Dian; Kalalo, Elisabeth (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Hotel tax is a type of tax that has potential in Bekasi City and the contribution to hotel tax revenue can encourage economic growth in Bekasi City. Apart from being a residential area, Bekasi City has also developed into a city of trade, services and industry. This development is in line with the increasing tax potential of the hotel type.This research aims to find out how effective hotel tax collection is in increasing local tax revenue in Bekasi City. This research uses descriptive qualitative methods with data collection techniques through interviews, observation and documentation. The analysis of this research was carried out by considering the Resource Approach, Process Approach and Goals Approach based on the effectiveness theory put forward by (Lubis & Husain, 2009). The results of the research show that hotel tax collection in increasing regional tax revenues in Bekasi City has not been effective. This can be seen from the many obstacles in collecting hotel tax in Bekasi City. Judging from the source approach, the competency of human resources is not evenly distributed and the use of information technology is not yet optimal. Judging from the process approach, there are four indicators, namely tax potential, taxpayer compliance, hotel tax collection system and monitoring and evaluation. An obstacle related to potential hotel taxes is the unavailability of current data containing information about hotel conditions. Another obstacle is the low level of taxpayer compliance and the inadequate use of information technology systems in the hotel tax collection process as well as the monitoring and evaluation process. Furthermore, looking at the target approach, it proves that the realization of hotel tax revenue from 2018 to 2023 has never reached 100% except in 2021, where the hotel tax revenue target was reduced due to the prolonged impact of COVID-19